The Influence of Social Media Marketing, Trust, Perceived Value and Preference on Intention to Study Undergraduate of Students at Rangsit University - Chanthai, Saksit; Lexcharoen, Somchai (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
The purposes of this paper aims to 1) develop and examine the consistency of the structural equation modeling regarding the intention to study an undergraduate program at Rangsit University and 2) investigate the causal factors influencing the intention to study in undergraduate programs at Rangsit University. This quantitative study focuses on social media marketing, trust, perceived value, preference and intention to study in an undergraduate program. The samples were collected from 502 undergraduate students at Rangsit University using convenience sampling, and the data were analyzed using descriptive statistics, Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). The research results indicated that the structural model demonstrated a good fit with the empirical data. Preference exerted the most significant direct effect on the intention to study, followed by perceived value. Conversely, trust had no direct effect but exhibited an indirect effect on the intention to study, mediated by preference. Additionally, social media marketing indirectly influenced the intention to study through the mediating roles of trust, perceived value, and preference, with a mediation proportion of 43.7%. mediating effect ratio. University administrators should prioritize social media marketing strategies to systematically build trust and perceived value, thereby gaining preference for driving intention to study an undergraduate program.